Determinants of State Civil Apparatus Performance with Work Environment as an Intervening Variable in the Regional Apparatus of Central Aceh District - Agustian; Syaifuddin; Fajar Rezeki Ananda Lubis (International Journal of Computational and Experimental Science and Engineering, 2025)
The decline in employee performance is largely caused by various internal and external factors of an organization. So that it causes losses to an organization itself. Therefore, this study will test the determinants of the performance of the State Civil Apparatus (ASN) with the work environment as an intervening variable. Data collection using quantitative methods and processing using Smart PLS. The study was conducted on 372 respondents who worked in the regional apparatus organization of Central Aceh Regency. The results of the study showed that work professionalism and Competence have an influence on the work environment. Furthermore, work professionalism and Competence also affect employee performance. In the indirect variable, professionalism and competence also affect performance which is intervening by the work environment. So it is concluded that all variables have an influence in improving employee performance in Central Aceh Regency. Keywords: Professionalism, Competence, Work Environment, State Civil Apparatus Performance